Religious Guidance for Muallaf in Rawa Mekar Village - Muhamad Dika Pransah; Aam Nur Komariah; Agus Suherman; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2022)
Religious conversion or so-called religious conversion sometimes often occurs in the layers of society arising from dissatisfaction with the existing reality so that they move from the old religion to the new religion. A person who has just embraced Islam or converts to Islam generally experiences several problems and it requires guidance from the community so that there is a sense of calm and comfort when converts mingle in society. With good guidance, it is hoped that it can increase faith and be true in carrying out Islamic law according to the terms and pillars that apply. This study aims to see the development of converts in exploring Islamic teachings and provide appropriate guidance according to the psychology of the object of research. The method we use in this study is a descriptive qualitative method by interviewing informants, observing the environment where he lives, and collecting documentation when the object of the research was still a Protestant Christian and when he converted to Islam. We took a sample of one of the two who were converts to Islam. The result we got was that the object we studied became converts to Islam because there was no coercion but because of a strong impulse because they were touched by hearing the call to prayer and having an Islamic environment.